National Security Transformation in the Context of Postmodernism as Modern Cultural, Social, and Political Reality - Levyk, Bogdan stepanovich (Journal of History Culture and Art Research, 2020)
The purpose of this article is to define the “security” concept, understand its historical content as methodological base of state national security, consider the phenomenon of “national security” and demonstrate that the legal foundation of the national security should be based on the traditional cultural and mental factors. The article also considers the postmodern state “metamorphosis” and concepts related to it. The author mentions that there is a lack of the appropriate methodological base for generalization, systematization and classification of information on the national security in scientific discourse. To resolve this, hermeneutic methodology and structural analysis have been used to achieve the stated purpose. The article concludes that Postmodernism, on the one hand, enabled new vectors of analytical understanding and perception of the security phenomenon, and on the other hand – by violating the established foundations and traditions (especially in the perception of the state institution) – introduced an imbalance and determined the crisis factor in the space of classical perception of security guarantors. The rejection factor is seen as a core feature of postmodern social-political reality. The article states the importance and priority of dealing with the problem of historical memory and actualizing the phenomenon of mentality in the context of future analytical discourses in the scope of Ukrainian security studies.